Implementation of the Merdeka Curriculum to Improve Learning Outcomes in Vocational High Schools (SMK) - Rahmawati, Rahmawati; Hidayat, Rais (Journal of Industrial Engineering & Management Research, 2024)
The Independent Curriculum is the Indonesian Government's policy in preparing students for learning outcomes in the implementation of the new curriculum. This research aims to find out how the implementation of the independent curriculum improves the learning outcomes of students at Development Technology Vocational School and Puja Bangsa Vocational School. The research method chosen in this research is a qualitative method in the form of data analysis (library research). Data collection techniques are carried out by interviews, observation and documentation. The source of information we got was from the Deputy Head of Curriculum. The results of the research show that the independent curriculum plays an important role in improving learning outcomes where the teaching and learning process can take place in an exciting way, filled with creativity and innovation which can later motivate students to learn, and teachers are also motivated to improve their professional abilities in teaching and learning activities, so that learning outcomes achieved. So the researcher can conclude that the Merdeka curriculum is freedom in determining how to behave, process, think, act creatively for the self-development of each individual by determining his own destiny. The implementation of the Independent Curriculum in improving learning outcomes is marked by the implementation of a learning process in which the teacher becomes a facilitator, mediator and motivator for students so that they are enthusiastic about learning.